L-arginine treatment in ischemia/reperfusion injury - Huk, I; Nanobashvili, J; Orljanski, W; Neumayer, Ch; Punz, A; Holzaepfel, A; Fuegl, A; Mittlboeck, M; Polterauer, P; Roth, E (Casopis lekaru ceskych, 1998)
We tested whether treatment with exogenous L-arginine, the precursor of nitric oxide (NO), could protect the skeletal muscle from ischemia/reperfusion (I/R) injury. A rabbit hindlimb I/R model (2.5 h ischemia/2 h reperfusion) was used. Morphological changes were elucidated by morphometry. Plasma concentrations of malondialdehyde (pMDA), as well as L-arginine and L-citrulline content in the plasma and skeletal muscle were measured. I/R injury in the skeletal muscle was manifested by development of prominent interstitial edema (fraction of interfiber area was 26.23% vs 15.09% in sham operated control, p < .005) and severe microvascular constriction (capillary area was 11.41 microns2 vs 16.92 in control, p <.005). These changes were accompanied by increased pMDA levels, indicating a process of lipid peroxidation in the cell membranes. L-arginine treatment (4 mg/kg/min intravenously, for 1 h, infusion initiated 30 min before reperfusion) caused an intracellular accumulation of this amino acid in the SM. Intracellular concentrations of L-citrulline increased (201.0 mumol/dm3 after reperfusion vs 176.0 before ischemia onset, p < .005), suggesting stimulated endogenous NO synthesis. L-arginine treatment protected capillary constriction (capillary area was 17.64 microns2 vs 11.41 in the untreated animals, p < .0005) and reduced interstitial edema after reperfusion (fraction of interfiber area was 17.80% vs 26.23 in untreated animals, p < 0.005). The protective effect of L-arginine treatment on I/R injury of SM may be related to its ability to prevent microvascular constriction and reduce permeability disorders by the stimulation of endogenous NO production.
Keywords: reperfuzní poškození; arginin; Arginine; zadní končetina; zvířata; Hindlimb; Muscle, Skeletal; králíci; Reperfusion Injury; kosterní svaly; Rabbits; Animals